The Response Inventory for Stressful Life Events (RISLE) I. refinement of the 100-item Version - Ovuga, Emilio; Boardman, Jed; Wasserman, Danuta (African health sciences, 2005)
No indigenous screening instruments are available for the detection of depression and suicide risk relevant to the context of patients in Uganda. The Response Inventory for Stressful Life Events (RISLE) may be an appropriate tool, but requires validation. Objective: The paper reports on the development of the RISLE and the refinement of the 100-item RISLE into a shorter version for use in large samples. Methods: Two samples were used in the validation exercise: a general population sample from Adjumani and Bugiri districts and a student sample from Makerere University in Kampala district. The RISLE responses were subjected to Principal Components Analysis and Discriminant Function Analysis. The 100-item RISLE and resulting shorter version were compared and their concurrent validity assessed by comparing test results to the individuals’ responses to the Beck Depression Inventory (BDI) and the Beck Scale for Suicide ideation (BSS). Results: Nine hundred thirty nine questionnaires were available for the population sample, 101 for the student sample. The 100- item RISLE was reduced to 36-items without loss of face validity. Both the 100- and 36-item versions had high internal consistency, were highly correlated with each other and with the BDI and BSS. Conclusion: The 36-item RISLE appears to be an advance on the 100-item version, retaining its internal consistency and concurrent validity.
Keywords: Response Inventory; Stressful Life Events (RISLE) I.; 100-item Version